The characteristics of hemophilic patients with decreased bone density in Cipto Mangunkusumo Hospital Jakarta - Anggoro, S; Setyohadi, B; Sukrisman, L; Setiati, S (Indonesian Rheumatology Association, 2013)
Background: Hemophilia can cause musculoskeletal complications and decreased bone density is one of those complications. The profile of hemophilic patients with decreased bone density in Indonesia is still unknown.Objective: To estimate the proportion of decreased bone density hemophilia and to learn the characteristics of hemophilic patients with decreased bone density.Methods: This is a cross-sectional study done in June - November 2012. Subjects were adult hemophilic patients from 19-50 years old in Hematology- Oncology outpatient clinic Cipto Mangunkusumo Hospital. Estimated variables were bone density mass, age, bodymass index, physical activity, arthropathy, substitution therapy, HIV, and HCV infection.Result: 63 subjects were included in the study with median age of 26 years old. The proportion of decreased bone density in hemophilia was 6.3%. Subjects with decreased bone density were younger (19 years old vs 26 years old), have lower BMI (18,6 + 2,8 kg/m2 vs 21,5 + 3,8 kg/m2), used more substitution therapy (4047 IU/month vs 2000 IU/month), and have better clinical arthropathy score. HCV infection happened on 25% subjects with decreased bone density while HIV was on 1.6% of subjects.Conclusion: Decreased bone density was found in 6.3% of subjects with hemophilia. They were younger, have lower BMI, better joint score, lower infection caused by transfusion, and more bleeding compared with subjects with normal bone density.